Filsafat Bahasa Al-Farabi dalam Kitāb al-Ḥurūf: Relasi antara Bahasa, Logika, dan Realitas - Sitti Maryam (VIRTUOUS JOURNAL, 2025)
This article examines the philosophy of language in the thought of Al-Farabi through his work Kitāb al-Ḥurūf. The primary focus of this study is the analysis of the relationship between language (lughah), logic (manṭiq), and reality (wujūd) within Al-Farabi’s epistemological and metaphysical framework. This research employs a qualitative method based on library research with a descriptive-analytical approach. The findings reveal that Al-Farabi conceives language as a symbolic representation of reality that is understood through the instrument of logic. He emphasizes that linguistic terms are closely connected to universal concepts, which constitute the proper objects of the intellect. Kitāb al-Ḥurūf also demonstrates Al-Farabi’s effort to reconcile Arabic linguistic terminology with the Greek philosophical tradition, particularly in relation to the understanding of logical and ontological categories. This article concludes that Al-Farabi’s philosophy of language is fundamentally integrative, as it unifies linguistic, logical, and ontological dimensions within a systematic and coherent framework.